2011
DOI: 10.4103/2230-973x.93004
|View full text |Cite
|
Sign up to set email alerts
|

Prefilled syringes: An innovation in parenteral packaging

Abstract: Parenteral administration of pharmaceutical products is one of the most popular methods used to produce quick onset of action and also 100% bioavailability. Main problem occurs with the parenteral drug delivery is lack of convenience, affordability, accuracy, sterility, safety etc. Such drawbacks with this delivery system makes it less preferable. Hence, all the disadvantages of these systems can be easily overcome by use of prefilled syringes. The objective of this review article is to provide information reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…Participants viewed the device's COP composition as generally neutral, with some considering it to be less likely to break than traditional glass syringes. While perhaps not perceptible to participants during the study, syringes made of plastic are known to have higher break resistance compared to typical glass syringes (35). This could potentially reduce the risk of breakage and associated complications during use or transport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants viewed the device's COP composition as generally neutral, with some considering it to be less likely to break than traditional glass syringes. While perhaps not perceptible to participants during the study, syringes made of plastic are known to have higher break resistance compared to typical glass syringes (35). This could potentially reduce the risk of breakage and associated complications during use or transport.…”
Section: Discussionmentioning
confidence: 99%
“…To date, marketed IVI medications are provided in glass primary containers (either vials or PFSs). Because of the potential for glass defects and the need for SO lubricant (35), novel polymer PFS devices are currently under development. The FDA recommends that manufacturers conduct human factors testing during the development of new medical devices to ensure they are safe and effective for the intended users, uses, and use environments.…”
Section: Introductionmentioning
confidence: 99%
“…These pharmaceutical preparations are graded as high risk . Like the magistral formulas, these preparations are based on the SmPC of a product and reconstitution by the pharmacy reduces risks of miscalculations and contamination . Reconstitution can be executed conform good nursing practice in clinical areas, where upscaling above a certain volume leads to increasing risks because a deficient product may affect the health of a considerable number of patients.…”
Section: Unlicensed Pharmaceutical Preparationsmentioning
confidence: 99%
“…6 Consequently, the development of self-injection devices has improved patient acceptance of injections, ease of use compared with the conventional needle and syringe, 7 and patient experience and preference. 8 Newer autoinjector technologies are designed to further ease patient burden, facilitate self-injection, and improve treatment adherence and convenience; 6,8 these are considered by healthcare professionals to be advantageous to manual syringe injections. 9 In a recent study, participants reported a high likelihood (86% very likely or somewhat likely) of adherence to treatment using an autoinjector device.…”
Section: Introductionmentioning
confidence: 99%